A sustainable approach tackling WEEE management using ontology-based DSS - Ismail Mohamed, Ahmed Tarek; Laviano, Francesco; Fino, Debora; Rubertelli, Francesca; Toscano, Claudio (Frontiers in Sustainability, 2025)
Electronic waste generation has been following a continuously rising trend. With electronics containing a myriad of materials some of which are hazardous, toxic, extremely rare, or precious combined with more stringent legislative laws which encourage the reuse and optimised recycling of the materials included in WEEE, the need for a holistic approach is inevitable. In the context of this research, the term holistic refers to the three aspects of material, technology, and hazard. This work aims to develop an approach that identifies the materials found in the various types of WEEE and their respective quantities as well as highlights the possible handling techniques and their respective impacts and associated hazards whether to the environment or human health. Performing such a task manually would be exasperating and costly while requiring extensive resources that might not be met with a justifiable economic gain; thus, the use of the advancement in computational sustainability to draw a complete framework and aid in an informed decision-making process is crucial. The WEEE ontology developed in this paper is one way of addressing the problem since it covers the treatment domain, the hazard and the materials contained within the different types of WEEE. The ontology developed in this research is part of a Decision Support System that is yet to be integrated, however, the ontology can be directly used from the commercial Protégé software.